2023
DOI: 10.1097/ana.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia Techniques in Modern Neuroanesthesia Practice: A Narrative Review of the Clinical Evidence

Abstract: Neurosurgical procedures are often associated with significant postoperative pain that is both underrecognized and undertreated. Given the potentially undesirable side effects associated with general anesthesia and with various pharmacological analgesic regimens, regional anesthetic techniques have gained in popularity as alternatives for providing both anesthesia and analgesia for the neurosurgical patient. The aim of this narrative review is to present an overview of the regional techniques that have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Adjuvants such as dexamethasone, magnesium sulfate, or both to local anesthetic agents for scalp block, has been shown to improve analgesia and patient satisfaction during awake craniotomies [27]. Moreover, ultrasound-guided scalp blocks are more efficacious than the landmark technique in terms of analgesia and duration of action [30,31 ▪▪ ].…”
Section: Perioperative Pathway: Fast-track Protocol For Same-day Neur...mentioning
confidence: 99%
See 2 more Smart Citations
“…Adjuvants such as dexamethasone, magnesium sulfate, or both to local anesthetic agents for scalp block, has been shown to improve analgesia and patient satisfaction during awake craniotomies [27]. Moreover, ultrasound-guided scalp blocks are more efficacious than the landmark technique in terms of analgesia and duration of action [30,31 ▪▪ ].…”
Section: Perioperative Pathway: Fast-track Protocol For Same-day Neur...mentioning
confidence: 99%
“…Regional anesthesia techniques, when compared to general anesthesia, have been associated with favorable hemodynamics, reduced incidence of intraoperative blood loss, deep vein thrombosis, pulmonary embolism, renal failure, and postoperative cognitive dysfunction [31 ▪▪ ]. A meta-analysis of 11 randomized controlled trials (RCT) comparing general anesthesia vs. spinal anesthesia in lumbar spine surgery, concluded that spinal anesthesia decreased postoperative pain and the analgesic requirement, along with reduced incidence of postoperative nausea and vomiting (PONV), and better patient satisfaction.…”
Section: Perioperative Pathway: Fast-track Protocol For Same-day Neur...mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, there are some high-quality prospective and randomized studies supporting the use of erector spinae blocks in thoracolumbar surgery, with promising data emerging for other cervical and truncal fascial plane blocks (including multifidius cervicis blocks, intersemispinal plane blocks, thoracolumbar interfascial plane blocks, and quadratus lumborum blocks, among others). 56,57 While an exhaustive description of these various regional techniques lies outside of the scope of this review, this is an area that holds great potential within the perioperative care of complex spine surgery patients, becoming part of standard care pathways and algorithms in some institutional practices.…”
Section: Perioperative Pain Controlmentioning
confidence: 99%